2006
DOI: 10.1007/s10517-006-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of fragments from transcribed region of ribosomal repeat on human peripheral blood lymphocytes

Abstract: Fragments from the transcribed region of the ribosomal repeat include considerable amounts of unmethylated CpG DNA motifs. These motifs activate immune cells via the interaction with Toll receptors. In vitro experiments confirmed the stimulatory effect of transcribed region of ribosomal repeat on human lymphocytes. Culturing of lymphocytes in a medium containing 2-20,000 ng/ml fragments from transcribed region of ribosomal repeat was accompanied by structural changes in the nucleus in a considerable number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…TRrDNA content in ecDNA samples was established using quantitative hybridization [1,3]. ecDNA was separated from blood plasma, obtained from patients with atherosclerosis and arterial hypertension II grade (1)(2)(3)(4) or arterial hypertension without signs of atherosclerosis (5).…”
Section: Human Umbilical Vein Endothelial Cells (Huvec)mentioning
confidence: 99%
See 1 more Smart Citation
“…TRrDNA content in ecDNA samples was established using quantitative hybridization [1,3]. ecDNA was separated from blood plasma, obtained from patients with atherosclerosis and arterial hypertension II grade (1)(2)(3)(4) or arterial hypertension without signs of atherosclerosis (5).…”
Section: Human Umbilical Vein Endothelial Cells (Huvec)mentioning
confidence: 99%
“…Accumulation of CG-DNA fragments in ecDNA is not indifferent for the cells, because they act as ligands interacting with TLR family proteins (TLR9) [3]. We previously showed that accumulation in ecDNA of one of repeating CG-DNA of human genome, transcribed region of ribosomal repeat (TRrDNA), containing binding sites for TLR9 can result in signifi cant lymphocyte activation accompanied by synthesis of proinfl ammatory cytokines [2]. In in vitro experiments, endogenous CG-DNAs accumulated in the blood of patients with cardiovascular diseases [1] reduced the rate of contraction of rat cardiomiocytes [7].…”
mentioning
confidence: 99%
“…Based on the conclusions made from the results of our studies of cfDNA properties, we determined the most significant cfDNA parameters, which can evoke biological responses in different cell types: Elevated GC-rich DNA content of the cfDNA, in particular, elevated ribosomal DNA (rDNA) content [ 14 , 52 ]. Increased content of oxidized DNA fragments [ 15 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Elevated GC-rich DNA content of the cfDNA, in particular, elevated ribosomal DNA (rDNA) content [ 14 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…3 The rDNA fragments activate immune system cells, and this interaction is accomplished by the binding of the CpG-rich rDNA motifs with the "toll"-like receptors (TLR9). 4 Since the cardiomyocytes express TLR9, 5 we would assume that for patients with AMI the CpG-rich fragments of the cfDNA influence myocardial cell operation. To examine the hypothesis, we studied the effect of different fragments of human DNA on the frequency of contraction of the electrically paced neonatal rat ventricular myocytes in culture.…”
Section: Introductionmentioning
confidence: 99%